2019
DOI: 10.1101/832311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reward certainty and preference bias selectively shape voluntary decisions

Abstract: 19Choosing between equally valued options can be a conundrum, for which classical decision 20 theories predicted a prolonged response time (RT). Paradoxically, a rational decision-maker 21 would need no deliberative thinking in this scenario, as outcomes of alternatives are indifferent. 22How individuals choose between equal options remain unclear. Here, we characterized the 23 neurocognitive processes underlying such voluntary decisions, by integrating advanced cognitive 24 modelling and EEG recording in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Interestingly, the theoretically optimal policy for the binary decision case ( Tajima et al, 2016 ) is inconsistent with empirical observations of magnitude-sensitive reaction-times ( Teodorescu et al ( 2016 ); Pirrone et al ( 2018a ); Steverson et al ( 2019 ); Zajkowski et al ( 2019 ); Turner et al ( 2019 ), but see Bhui ( 2019 )), unless assumptions are made that subjective utilities for decision-makers are nonlinear, or decisions are embedded in a fixed-length time period with known or learnable distributions of trial option values, so that a variable opportunity cost arises from decision time ( Tajima et al, 2016 ). Furthermore, even single-trial dynamics lead to magnitude sensitive reaction times ( Pirrone et al, 2018b ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the theoretically optimal policy for the binary decision case ( Tajima et al, 2016 ) is inconsistent with empirical observations of magnitude-sensitive reaction-times ( Teodorescu et al ( 2016 ); Pirrone et al ( 2018a ); Steverson et al ( 2019 ); Zajkowski et al ( 2019 ); Turner et al ( 2019 ), but see Bhui ( 2019 )), unless assumptions are made that subjective utilities for decision-makers are nonlinear, or decisions are embedded in a fixed-length time period with known or learnable distributions of trial option values, so that a variable opportunity cost arises from decision time ( Tajima et al, 2016 ). Furthermore, even single-trial dynamics lead to magnitude sensitive reaction times ( Pirrone et al, 2018b ).…”
Section: Introductionmentioning
confidence: 81%
“…Rederiving optimal policies to account for geometric (Marshall, 2019) or general multiplicative (Steverson et al, 2019) costs of time qualitatively changes them in the binary decision case, introducing magnitude-sensitive reaction times (Marshall, 2019;Steverson et al, 2019). However, disentangling these from nonlinear subjective utility is challenging, and cannot be excluded as an explanation for previous results (Teodorescu et al, 2016;Pirrone et al, 2018a;Steverson et al, 2019;Zajkowski et al, 2019;Turner et al, 2019;Bhui, 2019;Smith and Krajbich, 2019;Pirrone and Gobet, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the theoretically optimal policy for the binary decision case [3] is inconsistent with empirical observations of magnitude-sensitive reaction-times ( [5,[10][11][12][13][14], but see [15]), unless assumptions are made that subjective utilities for decision-makers are nonlinear, or decisions are embedded in a fixed-length time period with known or learnable distributions of trial option values, so that a variable opportunity cost arises from decision time [3]. Furthermore, even single-trial dynamics have been observed to lead to magnitude sensitive reaction times [16].…”
Section: Introductionmentioning
confidence: 86%
“…In the case of a perceptual decision such as deciding which of two stimuli is brighter, the magnitude is the overall brightness of the alternatives, so that two stimuli having brightness of 30 cd/m 3 and 60 cd/m 3 have a magnitude of 30 + 60 = 90 cd/m 3 . 'Magnitude-sensitivity' (often also referred to as 'value-sensitivity') refers to the result that performance in decision-making is affected by the magnitude of the alternatives [1,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In particular, for higher magnitude conditions, decision-makers show responses that are faster and more likely to be random (i.e., more likely to be incorrect when there is a correct alternative) [3,11,22].…”
Section: Size Mattersmentioning
confidence: 99%